2009
DOI: 10.1017/s1368980009005333
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and associated factors among under-fives and their mothers in Bushenyi district, Western Uganda

Abstract: Objective: To determine the prevalence of anaemia and associated factors among under-fives and their mothers in a rural area of Western Uganda. Design: A cross-sectional investigation using both qualitative and quantitative methods of data collection. Stratified multistage sampling methods were used to select the study sample. A haemoglobinometer was used to assess Hb levels in the blood. Setting: A rural district in Western Uganda. Subjects: Children aged 6-59 months and their mothers aged 15-49 years. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
6
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 30 publications
7
40
6
5
Order By: Relevance
“…Another study in Brazil also reported 36.6% prevalence of anaemia in children a rural area [17]. A study conducted in Western Uganda also showed a prevalence of 26.2% [10]. The increased prevalence in the current study could be due to geographical variations or the time the survey was carried out.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Another study in Brazil also reported 36.6% prevalence of anaemia in children a rural area [17]. A study conducted in Western Uganda also showed a prevalence of 26.2% [10]. The increased prevalence in the current study could be due to geographical variations or the time the survey was carried out.…”
Section: Discussionsupporting
confidence: 49%
“…Another cross-sectional study done in a rural setting in Western Uganda revealed that the prevalence of anaemia was 26.2%. The place of birth, the age of the child, complementary foods, formal education and nutrition knowledge of the mother were factors that were significantly associated with anaemia among the children [10].…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, lower findings were observed among children 6–59 months old in other developing countries of Africa including Western Kenya and Uganda with a prevalence rate of 26.2 and 25%, respectively [15, 20]. Even as compared to other developing countries like South East Asia and Nepal (40%), anaemia was more prevalent in the study area [21].…”
Section: Discussionmentioning
confidence: 67%
“…The association between higher maternal education and lower prevalence of anaemia is related to the realization that maternal education enables mothers' empowerment regarding health information and care for their children (5,16) .…”
Section: Methodsmentioning
confidence: 99%
“…Very few studies make use of representative population samples and therefore can neither evolve in the analysis of anaemia risk determinants nor contribute to the planning of effective measures for their control (4)(5)(6) . The WHO has recommended that population-based studies be developed to investigate the health and nutritional status of populations and that, among the study objectives, investigation of the prevalence and determinants of anaemia be included as a way of evaluating and supporting new government actions (1) .…”
mentioning
confidence: 99%